The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1021/acs.jpcc.6b11254
|View full text |Cite
|
Sign up to set email alerts
|

Step-doubling at Vicinal Ni(111) Surfaces Investigated with a Curved Crystal

Abstract: Vicinal surfaces may undergo structural transformations as a function of temperature or in the presence of adsorbates. Step-doubling, in which monatomic steps pair up forming double-atom high staircases, is the simplest example. Here we investigate the case of Ni(111) using a curved crystal surface, which allows us to explore the occurrence of step-doubling as a function of temperature and vicinal plane (miscut α and step type). We find a striking A-type ({100}-like microfacets) versus B-type ({111}-like) asym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…The asymetric broadening of the curves increases dramatically when comparing to the sharplypeaked histograms of panel figure 3(a). This drastic change in the shape of P(d) is common to other metal surfaces [7,8], but only in the present case the smooth histograms of figure 3(c) allow the observation of fine modulations on the right hand tail that can be fitted with a set of Gaussian functions, which suggest the presence of terrace-width fluctuations around preferred (or 'magic') d n values.…”
Section: Terrace-width Distribution: Step Lattice Models and Electronsupporting
confidence: 61%
See 3 more Smart Citations
“…The asymetric broadening of the curves increases dramatically when comparing to the sharplypeaked histograms of panel figure 3(a). This drastic change in the shape of P(d) is common to other metal surfaces [7,8], but only in the present case the smooth histograms of figure 3(c) allow the observation of fine modulations on the right hand tail that can be fitted with a set of Gaussian functions, which suggest the presence of terrace-width fluctuations around preferred (or 'magic') d n values.…”
Section: Terrace-width Distribution: Step Lattice Models and Electronsupporting
confidence: 61%
“…During the last decade, a number of studies have been aimed at systematically exploring vicinal surfaces using crystal samples with both spherical and cylindrical shapes, mostly metals [3][4][5][6][7][8][9], but also semiconductors [10]. Using such samples one can probe entire families of vicinal planes, and hence provide a comprehensive understanding of all physical-chemical properties connected to the presence of surface steps.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both techniques reveal the homogeneous wetting of the entire substrate by a single hBN monolayer, which in turn induces a deep structural transformation of the curved Ni substrate underneath. The bare c-Ni(111) surface is characterized by patterns of one- 40 20 distance (nm) 0 -12 and two-atom-high steps [63], but after hBN growth such simple step lattices transform into hill-and-valley structures of hBN-covered (111) terraces alternated with nanofacets oriented along other Ni crystal directions. Early studies of hBN grown on Ni(755) have already suggested substrate faceting [25] and here we confirm that the hBN monolayer growth leads to general faceting at all A-type and B-type vicinal planes.…”
Section: Hbn Monolayer Growth and Structurementioning
confidence: 99%